Numerical modeling of deformation oF THE ELEMENTS OF A multicomponent system subjected to dynamic load - Odinokov, Valeriy Ivanovich; Prokudin, Alexandr Nikolaevich (Computational Continuum Mechanics, 2010)
We present a method for constructing a numerical procedure and an algorithm for its numerical realization in order to determine the strain-stress state of the elements of a multicomponent system subjected to dynamic load. The system consists of elastic solid bodies and an incompressible Newtonian fluid. The capabilities of the method have been verified by studying the ice field destruction process. The results of numerical experiments are given.